Stable supercontinuum pulse generated by modulation instability in a dispersion-managed fiber. Issue 14 (5th August 2016) - Duan, Liang; Yang, Zhan-Ying; Zhao, Li-Chen; Yang, Wen-Li
Abstract : We study on non-linear localized waves on continuous wave background in a dispersion and non-linearity management fibre. We find a stable supercontinuum pulse can be generated from a small modulation on continuous wave in a proper management way, for which the pulse spectrum width and its growth rate can be controlled well by the management parameters. Additionally, we demonstrate a Kuznetsov–Ma breather like non-linear localized wave can exist in a periodic dispersion management fibre, and its spectrum evolution is distinctive from the Kuznetsov–Ma breather's.